Myocardial revascularization in heart failure with reduced ejection fraction - Haring, Bernhard; Bauersachs, Johann; Frey, Norbert; Hoppe, Uta C.; Doenst, Torsten; Boehm, Michael (Deutsches Ärzteblatt, 2025)
Background: Heart failure (HF) patients with reduced ejection fraction (HFrEF) now more commonly die of non-cardiovascular causes than they did in the past. In patients with both HFrEF and ischemic cardiomyopathy (as the cause of HFrEF or as an accompanying condition), the effect of myocardial revascularization-i.e. percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG)-on long-term outcome is unclear. Methods: This review is based on publications that were retrieved by a selective search of the literature for pertinent clinical studies and current guidelines. Results: Drug treatment for HFrEF has markedly prolonged these patients' survival. In a comparative study, HF pharmacotherapy was found to add an average of 8.3 years to the lifespan of a 55-year-old patient with HFrEF. Three of the four randomized controlled trials on revascularization procedures were conducted prior to the major pharmacotherapy improvements leading to better outcomes in HF patients over the past decade. These trial data indicate a long-term benefit from CABG compared to medical treatment alone in patients with HFrEF and severe coronary heart disease. For example, in the STICH trial, the hazard ratio for death from any cause after a follow-up time of nearly 10 years was 0.84 (95% confidence interval, [0.73; 0.97]). The role of pre-procedural myocardial viability and ischemia testing remains to be fully determined. The choice of method for myocardial revascularization should be discussed within an interdisciplinary cardiac team in consideration of the patient's symptoms and ischemic burden, the complexity of the coronary findings, as well as the patient's perioperative risk and current medical HF therapy. No RCTs comparing CABG to PCI are yet available. Conclusion: Optimal guideline-directed medical therapy is a key determinant of long-term survival in patients with HFrEF.
Gesehen am 03.11.2025